Politeness Strategies in Wiki-mediated Communication of EFL Collaborative Writing Tasks - Li, Mimi (IALLT Journal of Language Learning Technologies, 2012)
Informed by the theory of social constructivism and computer-mediatedcommunication (CMC), wiki-mediated collaborative writing has beenincreasingly implemented in second or foreign language classes.However, to date, no research has addressed students’ interaction andnegotiation of their social relationship during wiki-mediatedcollaboration. Drawing on politeness theory, particularly Brown andLevinson (1987)’s taxonomy of politeness strategies, this studyanalyzed the wiki-mediated discourse of one collaborative writinggroup in a Chinese EFL context. This particular writing groupconsisted of three EFL college students at a southwestern university inChina. This article examined specifically how this small group activelyengaged in social interaction by adopting politeness strategies duringasynchronous communication in a wiki “Discussion” module. Resultsrevealed that this small group used three types of politeness strategies,i.e. positive, negative, and bald on record skillfully, to establishfriendship, solidarity and respect while completing their collaborativewriting tasks smoothly and efficiently. This study validates the value oflinguistic politeness strategies in the analyses of social interactionoccurring in computer-mediated discourse and also suggests somepedagogical implications.